Nursing Care For Mrs. Y With Helplessness At Rojinhome Ikedaen Okinawa Japan - Ita apriliayani; Ririn Isma Sundari; Fia Muzayanah (International Journal of Health Engineering and Technology, 2026)
The increasing elderly population in Japan and Indonesia increases the risk of powerlessness in residents of care facilities such as Rojinhome Ikedaen. This case study aims to describe nursing care for Mrs. Y with powerlessness through the process of assessment, diagnosis, intervention, implementation, and evaluation for 3x24 hours. The type of research is a qualitative descriptive case study with a nursing process approach. The population of the elderly in the Finesu room (20 people), a single purposive sample of Mrs. Y (92 years old, diabetes). Instruments include assessment sheets (MMSE, social interaction), interviews, observations; thematic analysis with triangulation. The results showed a diagnosis of powerlessness (D.0092) related to unsatisfactory interpersonal interactions; coping promotion intervention (I.09312) increased interaction interest from 2 to 5 and social participation. Conclusion: Stepwise nursing care is effective in reducing initial powerlessness, a continuous protocol for full independence is recommended.